The MTHFR A1298C polymorphism and Breast Cancer Susceptibility: MTHFR A1298C and Breast Cancer Risk - Al-Sammarraie, Halah Khalid Ibrahim (Iraqi Journal of Cancer and Medical Genetics, 2025)
Background:Breast cancer (BC) is still a worldwide health problem with a high mortality rate in Iraq and other countries. reductase gene (MTHFR) controls cell DNA methylation, and any defect in this gene may lead to cancer development. Aim: The goal of this study was to investigate the associations of SNP (rs1801131) A1298C genetic polymorphism of MTHFR gene as well as its haplotypes with breast cancer risk among Iraqi females. Materials and Methods: The study included fifty individuals diagnosed with breast cancer and fifty healthy controls. The ages of the patients ranged between 25 and 67 years. For DNA extraction, 1 ml of peripheral blood from each individual was used. The A1298C polymorphism was detected with a previously prepared kit according to the manufacturer’s instructions. Taq-Man allelic discrimination assay was used for genotype identification. Then, p values were calculated via a chi-square test for statistical analysis. Results: DNA was successfully extracted from all the samples. The breast cancer patients and control groups all had frequency genotypes consistent with Hardy-Weinberg equilibrium (HWE) expectations. Logistic regression was used to assess the etiological risk of A1298C polymorphism in breast cancer cases. Breast cancer cases were more common in people with the heterozygous mutant AC genotype, which was significantly associated (p = 0.016; OR = 2.88; 95% CI: 1.29–6.4). The risk factor of the mutant AC genotype increased 2.88 times more than that for the wild type. Conclusions: According to the study results, there is a variation in the distribution of the genetic frequency of the MTHFR polymorphism between patients and control individuals, which is associated with increased etiological risk of the A1298C SNP (rs1801131) in breast cancer patients.